A novel method for assessing imaging quality of coded-aperture gamma-ray camera to radioactive plane source. (7th March 2023) - Zhao, Mingyang; Wang, Zhonghai; Zhu, Balin; Bai, Lixin; Zhou, Rong; Yang, Chaowen
Abstract: With the wide application of the coded-aperture gamma-ray camera in the field of nuclear radiation monitoring, research on its imaging performance of radioactive point sources has increasingly matured. However, because of the difficulty in obtaining complex radioactive plane sources with specific activity distributions, there is a lack of experimental research on imaging performance of such sources currently, the main focus being on simulation research and on-site imaging trials. In addressing the issue, we proposed a method to assess image quality of coded-aperture gamma-ray camera to such sources, and performed imaging experiments with a custom-made gamma-ray camera. Driven by a two-axis computer-numerical control (CNC) motion platform, a point source was moved through prescribed paths at a given velocity, from which a custom activity distribution plane source for coded-aperture imaging was constructed. Peak signal-to-noise ratio and structural index similarity were the two indicators used to evaluate the imaging quality of the plane source for seven distinct shapes. The results indicate that the imaging quality of the plane source imaged by our custom-made camera and constructed using our method is excellent with these two indicators being better than 17 dB and 0.996, respectively. Our method provides good reliability and practicality, and offers an alternative approach for assessing imaging quality of coded-aperture gamma-ray camera for complex radioactive plane sources.